2011
DOI: 10.1159/000333118
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Benefit Analysis of Endocrine Therapy in the Adjuvant Setting for Postmenopausal Patients with Hormone Receptor-Positive Breast Cancer, Based on Survival Data and Future Prices for Generic Drugs in the Context of the German Health Care System

Abstract: Background: Cost-effectiveness analyses have focused on aromatase inhibitors (AIs), but the results are inconsistent and disease-free survival has often been extrapolated to overall survival. The present study calculates the cost-effectiveness of 5 years of letrozole versus tamoxifen versus anastrozole in the context of the German health care system, using survival data from the Breast International Group (BIG) 1-98 study and the Arimidex, Tamoxifen, Alone or in Combination (ATAC) study and generic prices. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…This confirms that the introduction of the DRG system has led to the incorporation of DRG-implicated economic aspects and concepts into daily medical care. However many cost-effectiveness analyses are not helpful from the care providers' perspective because they often take an overall approach from a society's perspective [1], not explicitly addressing that cost-effective therapy might not be cost-covering for the clinic and care provider at all. In summary, the references found represent only partially the actual effect and influence of economic aspects in hospitals on breast cancer treatment within the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms that the introduction of the DRG system has led to the incorporation of DRG-implicated economic aspects and concepts into daily medical care. However many cost-effectiveness analyses are not helpful from the care providers' perspective because they often take an overall approach from a society's perspective [1], not explicitly addressing that cost-effective therapy might not be cost-covering for the clinic and care provider at all. In summary, the references found represent only partially the actual effect and influence of economic aspects in hospitals on breast cancer treatment within the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…10% have a tumor stage so advanced that primary cyto-reductive surgery is not performed. Additional costs for potential postoperative complications were not included [36,37].…”
Section: Tab 1: Input Datamentioning
confidence: 99%
“…Generic brands for chemotherapeutic agents as well as molecularly targeted drugs appear to be more affordable for the general population of LC patients in RCSs compared with the innovator brands. Although there are no published studies related to LC, generic drugs have been shown to be as effective as (both in vitro and in clinical practice) and more cost effective than innovator brands for breast, gynecological and colorectal cancers [112][113][114][115]. A 12-year review of bioequivalence studies by the US FDA showed that the mean difference between innovator drugs from their generic substitutes was less than 5% [116].…”
Section: Reviewmentioning
confidence: 99%